Hemodynamic instability due to Macklin effect in a patient with COVID-19: a case report - Ruiz-Laos, Santiago Gerardo (2022)
This is the case of a 49-year-old male with spontaneous pneumomediastinum due to Macklin effect, who presented comorbidities and was diagnosed with COVID-19. The patient was placed on life support but showed an unfavorable progression with hemodynamic instability, which led to obstructive shock caused by pneumomediastinum. Despite being an unusual clinical entity, it is important to know its approach, diagnosis and management in the intensive care units.